Feasibility of teleyoga for people with post COVID-19 condition– a mixed method design - Marie Lundberg; Leonie Klompstra; Lotti Orwelius; Mirjam Schimanke; Cecilia Olsson; Anna Strömberg (BMC Complementary Medicine and Therapies)
Abstract Background Evidence about rehabilitation of post COVID-19 condition is scarce. Yoga has been found beneficial in other chronic conditions and can be delivered in a digital format at home. The aim of the study was to explore the feasibility of teleyoga in persons with post COVID-19 condition by assessing adherence, safety, limited efficacy and experiences. Methods Pre-post mixed-method design. Participants were recruited from a post COVID-19 rehabilitation clinic. The intervention included standardised live-streamed teleyoga sessions twice/week for 7 weeks and individual yoga using a digital application during 12 weeks. Adherence to the teleyoga intervention was measured by registration of participation and by analysing the log in the application. Safety was measured by registration of serious adverse events. Limited efficacy examined trends in the predicted direction for better outcome in patients with a post-COVID condition in the 6-minute walk test, gait speed, cognition, health-related quality-of-life, mental distress, sleep and exercise motivation. We also assessed patients’ experiences after the intervention. Results Nine women and 2 men were enrolled, aged between 27 and 61 years, and duration of post COVID-19 3–12 months. Adherence: Half of the participants participated in more than 50% of the online yoga sessions. They enjoyed the digital format and the social aspect of the online yoga sessions. Some participants experienced that the yoga sessions of 60 min were too long. People with post COVID-19 felt motivated to participate, however they felt conflicted when other commitments took time away from yoga. Adherence to the yoga application varied, 6 patients used it less than 50% of the recommended time. Safety: Persons with post COVID-19 experienced symptoms due to their disease, which could increase during the yoga sessions that made it harder to participate. There were no reported serious adverse events. Limited efficacy: Participants expressed that they breathed more consciously and experienced relaxation and reduction of stress and anxiety. After 7 weeks of teleyoga there was a significant improvement in cognitive function (p-value = 0.048). No differences were found in the physical tests, health-related quality-of-life, anxiety and depression, sleep or in exercise motivation. Conclusion Adherence to the online yoga sessions was quite low and might be improved with shorter yoga sessions. Online yoga was safe, but some participants experienced an increase in symptoms. Teleyoga was associated with improved cognition, breathing and relaxation. The results show that online yoga could be feasible for people post COVID-19, but adaptation of the yoga-program may be required, especially as many patients experience an increase of symptoms. Furthermore, the teleyoga should be more flexible with regards to the duration and the number of sessions. As few participants were adherent to the application, the relevance and usefulness of this needs to be further explored.